Monitoring Sistem Keamanan Laci Kasir Dengan Fingerprint Berbasis Android - Mardia, Ahmad Muslih; Fitri, Iskandar; Ningsih, Sari (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
Internet of Things is becoming one of the trends in the world of technology. One of the uses of technology like this can be found in maintaining the security of a store. In this study, the mechanical cash register drawer lock will be replaced with fingerprint biometric recognition technology that exists in smart phones. Use of Solenoid doorlock as a substitute for cashier drawer locks. The fingerprint will be verified by the application to be matched with the database, then send data to the NodeMCU microcontroller which is integrated with smart phone devices as monitoring. The data will be sent to the database and read by the application system on the smart phone device to be accessed anywhere. Solenoid doorlock instead of drawer lock. If the fingerprint successfully verifies the fingerprint and matches the data in the system, the cashier drawer lock will open.
Keywords: Fingerprint; Selenoid Doorlock; Cashier Locker; Android; Monitoring